1999
DOI: 10.1007/pl00014327
|View full text |Cite
|
Sign up to set email alerts
|

Combined liver-kidney transplantation in primary hyperoxaluria type 1

Abstract: Primary hyperoxaluria type 1 (PH1) is a rare autosomal recessive disorder characterised by an increased urinary excretion of calcium oxalate, leading to recurrent urolithiasis, nephrocalcinosis and accumulation of insoluble oxalate throughout the body (oxalosis) when the glomerular filtration rate falls to below 40-20 mL/min per 1.73 m(2). The disease is due to a functional defect of the liver-specific peroxisomal enzyme alanine: glyoxylate aminotransferase (AGT), the gene of which is located on chromosome 2q3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 14 publications
1
46
1
2
Order By: Relevance
“…7,8 Early kidney transplantation is evidently sufficient to eliminate oxalate deposits at least partially and has the effectiveness to improve patient's condition without liver transplantation. 9 This option should be considered in pyridoxine-sensitive patients even in the existence of systemic oxalosis because of the good results of isolated kidney graft. 10,11 Allen et al identified a patient with clinical and biochemical existence of residual AGT activity and with a perfect renal function without the formation of a new calculus 1 year after renal transplantation from a live donor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Early kidney transplantation is evidently sufficient to eliminate oxalate deposits at least partially and has the effectiveness to improve patient's condition without liver transplantation. 9 This option should be considered in pyridoxine-sensitive patients even in the existence of systemic oxalosis because of the good results of isolated kidney graft. 10,11 Allen et al identified a patient with clinical and biochemical existence of residual AGT activity and with a perfect renal function without the formation of a new calculus 1 year after renal transplantation from a live donor.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this approach is not only to cease kidney involvement but also to prevent the progressive nature of oxalate deposition in other organ and soft tissues. 8,9,13,14 In this respect retinal examination gives opportunity to evaluate oxalate deposition. Small et al presented 24 patients with ocular involvement.…”
Section: Discussionmentioning
confidence: 99%
“…If the liver is normal but for the absence of an enzyme, the indications for liver replacement are based on poor quality of life, e.g. in Crigler-Najjar's disease, where phototherapy becomes excessively constrainingin the growing child [60], or on extrahepatic complications, as in primary hyperoxaluria type I (indication for combined liver-kidney transplantation, in order to avoid systemic oxalosis, when GFR falls to < 50 ml/min) [61]. When the enzyme deficit leads to liver cirrhosis (alpha-I antitrypsin deficiency, tyrosinaemia, Wilson's disease..…”
Section: A When the Enzyme Deficit Is Limited To The Liver (Crigler-mentioning
confidence: 99%
“…Kasiske et al (383). Although liver transplantation is potentially curative, there is no consensus regarding the timing of liver transplantation and the role of isolated kidney transplantation in treating patients with PH1 (384).…”
Section: The Evaluation Of Renal Transplant Candidates: Clinical Pracmentioning
confidence: 99%
“…However, the authors concluded that because kidney/liver transplantation can still follow a failed kidney transplant, isolated, living-related donor, kidney transplantation is a reasonable first option for patients with PH1 (389). Aggressive hemodialysis should be used to reduce the oxalate load pretransplant (383). Isolated kidney transplant should also be accompanied by intensive medical management to prevent recurrent renal disease (390,391).…”
Section: The Evaluation Of Renal Transplant Candidates: Clinical Pracmentioning
confidence: 99%